Inovasi Outer Kekinian Dengan Motif Kolaborasi Icon Dan Batik Jambi Disertai QR Code - Nazrul Musyafiq; Rosa Afri Herawati; Melisa Mentari; Wiliam Krishna; Fitri Setya Ningrum; Nurida Isnaeni (Journal of Management and Creative Business, 2024)
Jambi Province, located in the center of Sumatra, has developed creativity in batik crafts with various distinctive batik motifs. Apart from that, this province also has historical heritage, such as the Muaro Jambi Temple, which is a witness to the glory of the past. It is important to study this aspect scientifically to ensure its preservation as part of cultural heritage that can enrich people's lives. In an effort to preserve culture, we are organizing the "Outer Kito" product creation program as a method that can be implemented in everyday life in the millennial world. This product not only functions as a form of creativity in batik crafts, but also has historical value with the QR Code which provides information related to batik and the meaning it contains. Using "Outer Kito" products is expected to be a real step for the community to participate in preserving their culture.